Experimental study on performance of a biogas engine driven air source heat pump system powered by renewable landfill gas. (February 2016) - Wu, Jiying; Ma, Yimin
Highlights: The configuration of an LFG fueled biogas engine driven heat pump was studied. Waste heat can be recovered from exhaust fume or cylinder liner by switching valves. The testing platform of an LFG fueled biogas engine driven heat pump was built. The water pump and the fan of heat pump were all powered by the biogas engine. Variation of system COP and PER was tested under various biogas engine speeds. Abstract: The equipment configuration of a landfill gas (LFG) fueled biogas engine driven air source heat pump system was studied. The process flow for collecting and purifying LFG was analyzed, and the LFG collection and purification method was determined. An experimental apparatus was set up, and the effect of biogas engine speed variation on LFG consumption, exhaust fume temperature of biogas engine, recovered waste heat from exhaust fume and cylinder liner, coefficient of performance (COP) of the heat pump and primary energy ratio (PER) of the system were experimentally tested. The results indicated that LFG consumption and biogas engine exhaust fume temperature increased with biogas engine speed. When the biogas engine operated in the 70%–90% rated speed range, the system heat output and exhaust fume waste heat recovery rate would be relatively higher. In addition, the maximum COP and PER reached 4.2 and 1.4 respectively.